Post-processing of engineering products obtained by additive layer modelling - V.M. Orel; T.F. Kozlovs'ka; O.F. Salenko; P.P. Melnychuk (Технічна інженерія)
The article investigates the influence of mechanical post-treatment on the geometric and physical and mechanical characteristics of products manufactured by additive layer modelling (in particular, FDM). The mechanisms of formation of the defective layer arising from the hollow, anisotropic structure of the material, as well as temperature and force loads are considered. For the case of modelling a workpiece created by additive processes, it is necessary to take into account the hollowness of the workpiece body, as well as its layering and componentry. On the basis of numerical modelling, the stress-strain state of the workpiece during cutting, as well as the peculiarities of the distribution of deformations and stresses between fibres and layers, are determined. The influence of the cutting tool geometry, cutting modes, and structural features of the PLA material on the quality of the machined surface was investigated. Experimental tests of various post-processing methods were carried out i.e., turning, milling, drilling, and grinding. The obtained results confirm the need to limit cutting forces and use sharpened tools. Practical recommendations for optimising the post-processing of FDM-printed products are proposed. Prospects for further research, in particular, in the direction of taking into account the rheological properties of materials, are indicated.